Mcl-1 Inhibition: Managing Malignancy in Multiple Myeloma - Al-Odat, Omar S.; von Suskil, Max; Chitren, Robert J.; Elbezanti, Weam O.; Srivastava, Sandeep K.; Budak-Alpddogan, Tulin; Jonnalagadda, Subash C.; Aggarwal, Bharat B.; Pandey, Manoj (Frontiers in Pharmacology, 2021)
Cancer begins when cells start to grow out of control. This phenotype is acquired via a combination of increased cell growth and reduced occurrence of apoptosis. The expression of anti-apoptotic proteins of the Bcl-2 family, particularly myeloid cell leukemia-1 (Mcl-1), play a crucial role in the survival and existence of MM cells through the avoidance of programmed cell death. Selective inhibition of the Mcl-1 protein is regarded as a solid anti-myeloma strategy through the restoration of normal cellular apoptosis. Over the last decade, the development of selective Mcl-1 inhibitors has seen remarkable progress and this new class of drug appears to now be a viable opportunity to help overcome the current challenges in MM treatment. This literature presents the most prominent BH3 mimetic and semi-BH3 mimetic selective Mcl-1 inhibitors, the roles they can play in both monotherapy and combination therapies for the treatment of Mcl-1 dependent cancers, how this new avenue of treatment will help open new doors for MM patients and showcase a new successful and promising strategy in the BH3 mimetic drug class.